Analisis Penggunaan Media Pembelajaran Interaktif Canva dalam Pembelajaran Pendidikan Pancasila Kelas IV SDN 2 Bendogerit - Ramadhani, Nova Laurina; Astuti, Tri (EduInovasi: Journal of Basic Educational Studies, 2025)
This research was conducted at SDN 2 Bendogerit Blitar in the even semester of 2024/2025 which examines the use of canva-based interactive power point learning media in learning grade IV Pancasila Education. This study aims to analyze the use of Canva-based interactive power point learning media, the obstacles faced in using Canva-based interactive learning media in learning, and efforts that can be made to overcome the obstacles that occur in the use of Canva media in learning Pancasila Education grade IV SDN 2 Bendogerit. The research method and research approach used in this research is a descriptive qualitative approach with data collection techniques in this study include interviews, observation, and documentation. To ensure data validity, source triangulation and technique triangulation were used. Meanwhile, data analysis was conducted using the Miles and Huberman model, which includes three main stages: data reduction, data presentation, and conclusion drawing. Based on the results of research on the use of Canva interactive media in learning Pancasila Education in class IV SDN 2 Bendogerit, it can be concluded that the utilization of this media has a positive contribution and impact on the learning process and results of students. The use of Canva not only clarifies the material, but also supports a fun, varied, and appropriate learning approach.